Photoswitching Behavior of a Cyclohexene‐Bridged versus a Cyclopentene‐Bridged Dithienylethene System. Issue 7 (20th February 2015) - Steenbock, Torben; Escribano, Alejandra; Heck, Jürgen; Herrmann, Carmen
Abstract Photoswitching is an intriguing way of incorporating functionality into molecules or their subunits. Dithienylethene switches are particularly promising, but have so far mostly been studied with five‐membered ring (cyclopentenyl) backbones. We aim at comparing the switching properties of backbones with five and six carbon atoms in the ring. A major advantage is that cyclohexenyl rings offer new options for chiral functionalization. A slight change in the reaction conditions of a McMurry ring closure reaction leads to the formation of dithienyl derivatives with a cyclohexene backbone in reasonable yield. Density functional theory calculations were carried out, demonstrating the similarity of both compounds. Experimental results confirm the theoretical outcomes.